Cesarean sections and early-term births according to Robson classification: a population-based study with more than 17 million births in Brazil - Aline S. Rocha; Enny S. Paixao; Flavia Jôse O. Alves; Ila R. Falcão; Natanael J. Silva; Camila S. S. Teixeira; Naiá Ortelan; Rosemeire L. Fiaccone; Laura C. Rodrigues; Maria Yury Ichihara; Mauricio L. Barreto; Marcia F. de Almeida; et al. (BMC, 2023)
Abstract Background Cesarean section (CS) rates are increasing worldwide and are associated with negative maternal and child health outcomes when performed without medical indication. However, there is still limited knowledge about the association between high CS rates and early-term births. This study explored the association between CSs and early-term births according to the Robson classification. Methods A population-based, cross-sectional study was performed with routine registration data of live births in Brazil between 2012 and 2019. We used the Robson classification system to compare groups with expected high and low CS rates. We used propensity scores to compare CSs to vaginal deliveries (1:1) and estimated associations with early-term births using logistic regression. Results A total of 17,081,685 live births were included. Births via CS had higher odds of early-term birth (OR 1.32; 95% CI 1.32-1.32) compared to vaginal deliveries. Births by CS to women in Group 2 (OR 1.50; 95% CI 1.49-1.51) and 4 (OR 1.57; 95% CI 1.56-1.58) showed the highest odds of early-term birth, compared to vaginal deliveries. Increased odds of an early-term birth were also observed among births by CS to women in Group 3 (OR 1.30, 95% CI 1.29-1.31), compared to vaginal deliveries. In addition, live births by CS to women with a previous CS (Group 5 - OR 1.36, 95% CI 1.35-1.37), a single breech pregnancy (Group 6 - OR 1.16; 95% CI 1.11-1.21, and Group 7 - OR 1.19; 95% CI 1.16-1.23), and multiple pregnancies (Group 8 - OR 1.46; 95% CI 1.40-1.52) had high odds of an early-term birth, compared to live births by vaginal delivery. Conclusions CSs were associated with increased odds of early-term births. The highest odds of early-term birth were observed among those births by CS in Robson Groups 2 and 4.